Reliability of assessing skeletal muscle architecture and tissue organization of the gastrocnemius medialis and vastus lateralis muscle using ultrasound and spatial frequency analysis - Lesinski, Melanie; Bashford, Gregory; Markov, Adrian; Risch, Lucie; Cassel, Michael (Frontiers in Sports and Active Living, 2024)
The purpose of this study was to investigate inter-and intra-rater reliability as well as the inter-rater interpretation error of ultrasound measurements assessing skeletal muscle architecture and tissue organization of the Gastrocnemius Medialis (GM) and Vastus Lateralis muscle (VL).The GM and VL of 13 healthy adults (22±3 years) were examined thrice with sagittal B-mode ultrasound: intraday test-retest examination by one investigator (intra-rater) and separate examinations by two investigators (inter-rater). Additionally, images from one investigator were analysed by two interpretators (interpretation error). Muscle architecture was assessed by muscle thickness [MT], fascicle length [FL], as well as superior and inferior pennation angle [PA]. Muscle tissue organization was determined by spatial frequency analysis (SFA: peak spatial frequency radius, peak -6dB width, PSFR/P6, normalized peak value of amplitude spectrum [Amax], power within peak [PWP], peak power percent). Reliability of ultrasound examination and image interpretation are presented as intraclass correlation coefficient (ICC), test-retest variability, standard error of measurement as well as bias and limits of agreement.Results: GM and VL demonstrated excellent ICCs for inter-and intra-rater reliability, along with excellent ICCs for interpretation error of MT (0.91-0.99), showing minimal variability (<5%) and SEM% (<5%). Systematic bias for MT was less than 1 mm. For PA and FL poor to good ICCs for inter-and intra-rater reliability were revealed (0.41-0.90), with moderate variability (<12%), low SEM% (<10%) and systematic bias between 0.1-1.4°. Tissue organization analysis indicated moderate to good ICCs for inter-and intra-rater reliability.Notably, Amax and PWP consistently held the highest ICC values (0.77-0.87) across all analyses but with higher variability (<24%) and SEM% (<18%), compared to lower variability (<9%) and SEM% (<8%) in other tissue organization parameters. Interpretation error of all muscle tissue organization parameters showed excellent ICCs (0.96-0.999) with very low variability (≤1%) and SEM% (<2%), except Amax & PWP (TRV%:<6%; SEM%:<7%).Our findings demonstrated excellent inter-and intra-rater reliability for MT.However, agreement for PA, FL, and SFA parameters was not as strong. Additionally, MT and all SFA parameters exhibited excellent agreement for inter-rater interpretation error. Therefore, the SFA seems to offer the possibility of objectively and reliably evaluating ultrasound images.